The Analysis of Business Development Through Canvas Business Model Approach for Determining Post-pandemic Business Strategy: A Case Study in Smartplus Training and Consultant Management - Maulana, Muhammad Irfan; Sumadhinata, Yelli Eka (Jurnal Maksipreneur, 2023)
In 2020, Indonesia experienced a period of deflation or a drop drastic in the development of the economy caused there is a Covid-19 pandemic. At the moment, the Indonesian government has various policies for community and actors' efforts to restore return Indonesian economy. The destination of the study is to help analyze development efforts in determining a strategy for the business post-pandemic through the canvas model business. The research object is the Smartplus Training and Management Consultant actors. The business model canvas method is used to develop business models to increase competitiveness. The results from this research showed that the need exists to change targets and add customer segments. So that could increase the value proposition, namely change target revenue streams with optimizing revenue in sales. It also adds to the customer segment obtained from online media, and with the existence change key resources will change key activities, and to support development efforts consultants need additional investment funds.